Experimental Investigation and Comparison of the Net Energy Yield Using Control-Based Solar Tracking Systems - Ibrahim Sufian Osman; Ibrahim Khalil Almadani; Nasir Ghazi Hariri; Taher Saleh Maatallah (International Journal of Photoenergy)
As the world trend is going towards renewable energy, solar photovoltaic (PV) energy shines the most due to the low generation cost especially by using the latest PV cell technologies and materials, although the conventional silicon cell has an efficiency in the range of 15-16%. A PV tracking system (PVTS) could be a considerable method to increase electrical PV efficiency. In this study, the performance enhancement of the daily output power and energy has been experimentally investigated using single- and dual-axis tracking mechanisms for flat-plate conventional PV panels under the insolation conditions of the Eastern province of Saudi Arabia (SA). In the current study, the active PVTS has been designed and implemented with PID controllers and controlled in real-time with an embedded system. The fixed-tilt (FTPV), single-axis solar tracking system (SAST), and dual-axis solar tracking system (DAST) were tested simultaneously under clear-sky conditions. The PV electrical energy balance has revealed that the energy consumed by the electrical controllers of the SAST and DAST is 3.4% and 3.9%, respectively. In addition, the energy losses due to the actuators of the SAST and DAST are 7.8% and 13.0%, respectively, where they contributed mainly to the energy losses. However, the PV energy production by the DAST was high enough to compensate for the higher actuating mechanism losing rate compared to the SAST and performed incremental net energy output of around 8.64%. On other hand, the DAST and SAST were more efficient than the FTPV recording higher net energy increase by 28.98% and 18.73%, respectively.